the effect of gallery walk technique on students’ ability in writing hortatory exposition text (a study at the eleventh grade students of sma swasta katolik sibolga in 2018/2019 academic year) - Aloysia Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The objective of this research is to know whether there is a significant effect of gallery walk technique on students’ ability in writing hortatory exposition text at the eleventh grade students of SMA Swasta Katolik Sibolga in 2018/2019 Academic Year. This research uses experimental method with pre-experimental research design; one group pretest-posttest design. The population is all of the eleventh grade students which consists of 194 students. Technique sampling that is used on this research is systematic sampling and the number of the samples are 30 students. In collecting the data, the researcher uses observation sheet to get the data of the application of gallery walk technique and test to get the data of the students’ ability in writing hortatory exposition text. The researcher uses statistic process in analyzing the data by using ttest formula. Based on the data that had been analyzed, the result of data analyzing showed that ttest is higher than ttable (ttest 17.08 > ttable 2.04). So, the hypothesis is accepted. It means that there is a significant effect of gallery walk technique on students’ ability in writing hortatory exposition text at the eleventh grade students of SMA Swasta Katolik Sibolga in 2018/2019 Academic Year.